DARI TANAH MENUJU KESADARAN ILAHIAH: REKONSTRUKSI KONSEP EVOLUSI SPIRITUAL DALAM FILSAFAT ISLAM KONTEMPORER - Mastori, Mastori; Hadi, Abdul; Faqihuddin, Ahmad; Milasmawati, Milasmawati; Hidayah, Muhammad Syarif (Spektra: Jurnal Ilmu-ilmu Sosial, 2024)
Abstract( In English). This article explores the integration of Islamic creation narratives with modern evolutionary theory through a philosophy of consciousness approach. By analyzing the thoughts of Muhammad Iqbal and Nidhal Guessoum in dialogue with transpersonal psychology (Kitson et al., Yaden) and the philosophy of consciousness (Chalmers), this study proposes the concept of the "spiritual evolution of consciousness" as an alternative framework to materialistic reductionism. The findings suggest that the concepts of human creation from clay (Quran 1:12) and the breath of the spirit (Quran 1:29) can be understood as stages in the development of consciousness from biological consciousness to transcendental consciousness. This model offers a new paradigm in Islamic studies that reconciles science and spirituality while opening insights for the development of contemporary Islamic psychology.